ILLOCUTIONARY ACTS IN YUSUF MANSUR’S SPEECH ENTITLED BERBICARALAH YANG BAIK ATAU DIAM - WARDHANI, RIZA MAYTA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Illocutionary Act, Syntactic Realization, Yusuf MansurSpeech act is a way of expressing human’s thought through words. In speech act, the presence of particular utterances can even be used to perform actions by using gesture or body language. Moreover, since illocutionary acts as one of the speech act parts that have grammatical form of utterances as the representation, a speaker may realize his or her utterances in different ways. The writer focuses her study on the types of illocutionary act found in Yusuf Mansur’s speech entitled Berbicaralah yang Baik atau Diam. There are two problems to be solved in the study, namely (1) what types of illocutionary acts are found in Yusuf Mansur’s speech entitled Berbicaralah yang Baik atau Diam; and (2) how the illocutionary acts are syntactically realized.This study uses qualitative approach in relation to the use of clear and systematic description about the phenomena being studied. Descriptive study in textual analysis is applied in this study to analyze the transcribed script of Yusuf Mansur’s speech.The research findings show that there are 150 utterances containing illocutionary act in this study. There are, 94 utterances containing assertives, 3 utterances containing directives, 30 utterances containing commisives, 6 utterances containing expressive, and 17 utterances containing declarations. The majority type is assertives which means that the speaker tends to use assertive type in uttering his statement. However, almost all illocutionary acts are syntactically realized by using declarative sentence. There are 111 declarative sentences, 5 interrogative sentences, and 34 imperative sentences. Based on this research, it is found that illocutionary actcan be produced in most of utterances.The writer suggests English Department students find other theories concerning the notion of speech act and illocutionary act. She also suggests the next researchers investigate other elements of speech act since this study only covers illocutionary acts of someone’s utterances.